Update on Perioperative Ischemic Optic Neuropathy Associated With Non-ophthalmic Surgery - Roth, Steven; Moss, Heather E. (Frontiers in Neurology, 2018)
Perioperative visual loss (POVL) is a rare, serious complication of non-ophthalmic surgeries. Ischemic optic neuropathy (ION), and retinal arterial occlusion (RAO) are principal causes. Others include cortical blindness, acute glaucoma, and choroidal and vitreous hemorrhage. ION is the most common cause for which the neurologist or neuro-ophthalmologist is consulted as it is associated either with a normal ophthalmic exam, or, more rarely, with optic nerve (ON) head swelling. The most common surgical procedures complicated by ION are cardiac surgery and spinal fusion. Retrospective studies, surveys, and case reports provide much of the knowledge on peri-operative ION. Lack of controlled studies, and poorly defined risk factors still limit understanding of ION, although a number of recent studies are yielding increasing understanding, and an animal model of perioperative ION has recently been described. This mini-review will update the reader on the latest advancements regarding perioperative ION in epidemiology, clinical, and animal studies.